2020
DOI: 10.1002/ptr.6825
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin is a novel and selective IMPDH2 inhibitor that target triple‐negative breast cancer

Abstract: Triple‐negative breast cancer (TNBC) is heterogeneous disease with a poor prognosis. It is therefore important to explore novel therapeutic agents to improve the clinical efficacy for TNBC. The inosine 5′‐monophosphate dehydrogenase 2 (IMPDH2) is a rate‐limiting enzyme in the de novo synthesis of guanine nucleotides. It is always overexpressed in many types of tumors, including TNBC and regarded as a potential target for cancer therapy. Through screening a library of natural products, we identified shikonin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Guo et al ( 37 ) also found that shikonin inhibited cell proliferation and induced apoptosis in glioma. Wang et al ( 38 ) reported that shikonin inhibited the proliferation and promoted apoptosis of breast cancer cells. The results of the present study demonstrated that shikonin could inhibit proliferation, migration and invasion, and increase the apoptosis of A549 cells in a dose-dependent manner, which were consistent with the findings of previous studies ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al ( 37 ) also found that shikonin inhibited cell proliferation and induced apoptosis in glioma. Wang et al ( 38 ) reported that shikonin inhibited the proliferation and promoted apoptosis of breast cancer cells. The results of the present study demonstrated that shikonin could inhibit proliferation, migration and invasion, and increase the apoptosis of A549 cells in a dose-dependent manner, which were consistent with the findings of previous studies ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (38) reported that shikonin inhibited the proliferation and promoted apoptosis of breast cancer cells. The results of the present study demonstrated that shikonin could inhibit proliferation, migration and invasion, and increase the apoptosis of A549 cells in a dose-dependent manner, which were consistent with the findings of previous studies (36)(37)(38). However, the results of the present study showed a lower apoptosis rate, which is different to the results obtained in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…MDA-MB-231 and 4T1 were selected, for further investigation since they are highly invasive TNBC breast cancer cell lines [18], [19]. The 4T1 tumor is highly tumorigenic; unlike most tumor models, it can spontaneously metastasize from the primary tumor in the mammary gland to multiple distant sites [20].…”
Section: Discussionmentioning
confidence: 99%
“…It observably inhibited cell viabilities of MDA‐MB‐231 and 4T1 in a dose‐dependent manner with IC 50 of 2.08 and 1.45 μM, respectively. It stabilized IMPDH2 in MDA‐MB‐231 and 4T1 cells in cellular thermal shift assay (CETSA), illustrating that shikonin inhibited IMPDH2 directly in TNBC cells [55] …”
Section: Natural Products With Anti‐tnbc Activitiesmentioning
confidence: 98%
“…It stabilized IMPDH2 in MDA-MB-231 and 4T1 cells in cellular thermal shift assay (CETSA), illustrating that shikonin inhibited IMPDH2 directly in TNBC cells. [55] OHPer-MAng (25) (Figure 8) was isolated from the roots of the vegetable specimen A.cordata obtained (Dec. In the docking models, OHPer-MAng establishes great non-bonding interactions with the lateral chains of Tyr235, Hys201, Tyr246, Ser203, Asn207, and Gly233 located at the catalytic site of PARP-1.…”
Section: Terrestrial Natural Productsmentioning
confidence: 99%